Can palliative care reduce futile treatment? A systematic review. Issue 4 (28th January 2013) - Harris, Iain; Murray, Scott A
Abstract : Background: Palliative care interventions have the potential to lower health service costs by reducing the intensity of treatments intended to have curative effect while concentrating on quality of life and, in due course, quality of death. A patient receiving treatment inspired by curative intent during the end stage of their life is potentially exposed to medical futility. Aim: To conduct a systematic review of the evidence for palliative interventions reducing health service costs without impacting on quality of care. Method: An electronic search of MEDLINE, EMBASE, AMED and CINAHL databases, augmented by hand-searching techniques, was performed. Only research where palliative care was the intervention or observation, and cost, together with either quality of life or patient satisfaction with care were outcome measures, was included in results. Results: Of 1964 sources identified, only 12 measured both cost and an appropriate quality outcome. Evidence supported existing research that palliative care interventions generally reduce health service costs. Evidence of concurrent improvement in quality-of-life outcomes was limited; little available evidence derives from randomised trial designs. Small sample sizes and disparate outcome measures hamper statistical assessments. Conclusions: Evidence that palliative interventions cut costs, without reducing quality of life, by minimising futile medical acts is limited. Further research, including both observational studies and controlled trials, should be conducted to collect empirical data in this field. Future research should examine palliative interventions earlier in chronic progressive illness, and incorporate standardised outcome measures to allow meta-analysis.